2011
DOI: 10.1002/ceat.201000411
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Behaviors in Gas‐Solid Two‐Phase Magnetic Fluidized Beds 1. Experimental Results Represented by a Dimensionless Number

Abstract: The influence of magnetic field intensity and process parameters on the transient fluidization behaviors of magnetically stable fluidized beds (MSFBs) was studied. The local solid holdup distribution and magnetically stabilized regimes were carried out by experimental measurements in MSFBs. The scaling approach for MSFB hydrodynamics based on magnetic field and dynamic similitude with a limited number of dimensionless groups was tested. A dimensionless number for magnetic field has been developed. An experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The gas-solid magnetically fluidized bed (MFB) has been regarded as a useful process intensification strategy and has attracted increasing interest in industrial applications such as petroleum chemical processes, fine-chemical production and separation processes, because of the major advantages of good residence time distribution, small bubble size, low pressure drop, and a wide operation range of flow velocity [1][2][3][4][5][6]. Recently, some published articles indicated that an MFB demonstrates better performance in various circumstances when it is pressurized.…”
Section: Introductionmentioning
confidence: 99%
“…The gas-solid magnetically fluidized bed (MFB) has been regarded as a useful process intensification strategy and has attracted increasing interest in industrial applications such as petroleum chemical processes, fine-chemical production and separation processes, because of the major advantages of good residence time distribution, small bubble size, low pressure drop, and a wide operation range of flow velocity [1][2][3][4][5][6]. Recently, some published articles indicated that an MFB demonstrates better performance in various circumstances when it is pressurized.…”
Section: Introductionmentioning
confidence: 99%